Holocene environmental history of tropical, mid-altitude Lake Ocotalito, México, inferred from ostracodes and non-biological indicators. (September 2017) - Díaz, Karen A; Pérez, Liseth; Correa-Metrio, Alexander; Franco-Gaviria, Juan Felipe; Echeverría, Paula; Curtis, Jason; Brenner, Mark
This paleolimnological study used ostracodes assemblages, element concentrations, organic and inorganic carbon content, organic C:N ratios, and stable isotope values in valves of the ostracodes Cytheridella ilosvayi as paleoindicators and is the first such investigation from a mid-elevation site in southern México. We provide a 7600-year (9540–1970 BP) environmental history from karst Lake Ocotalito (920 m a.s.l.), which lies in the Lacandon Forest of Chiapas, México. A 5.4-m sediment core was retrieved from a water depth of 23 m. The main factor that shaped ostracodes species assemblages throughout the Holocene was lake level. A total of six species were identified, and the benthic Cytheridella ilosvayi was dominant. Less abundant species included nektobenthic taxa Cypridopsis okeechobei, Heterocypris putei, and Potamocypris sp. and benthic species Darwinula stevensoni and Pseudocandona sp. Wet conditions, high lake levels (>15 m), and low ostracodes abundances characterized the period between 9540 and 7820 BP. From 7750 to 6460 BP, indicators point to stable conditions and intermediate lake levels ( 15 m). Greatest ostracodes abundance and diversity occurred from 6200 to 4030 BP, during which mainly drier conditions were inferred, interrupted by short, humid periods. Lower abundances and low Sr and δ 18 O values characterized the period from 3810 to 1970 BP and indicate higher lake levels, that is, wetter conditions. Throughout this period, however, a slight trend toward drier conditions was observed. Comparison with paleolimnological studies in other karst lakes from the region suggests mid-altitude aquatic ecosystems may be more sensitive to climate fluctuations than lakes in the lowlands. For instance, stable isotope records from the Lake Ocotalito core display greater ranges. This, however, may simply reflect inter-lake differences in sensitivity, controlled by lake-specific hydrologic factors. The record from Lake Ocotalito fills an important gap in our knowledge of past biotic diversity, paleoclimate, and paleoenvironmental conditions in the northern Neotropics.